Something's phishy : a communications campaign designed to teach young adults to combat phishing threats - Tan, Amanda Yan (2019)
This paper presents Something’s Phishy, a communications campaign designed to teach young people aged 18-25 years old, to combat phishing threats. The campaign is initiated by four final-year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. Phishing is Singapore’s most common cyber threat, constituting 39% of cyber threats reported to SingCERT in 2017. Based on formative research findings and the Extended Parallel Process Model, the team developed an integrated communications campaign utilizing marine life imagery. The campaign featured an edutainment online video series and campaign roadshows carried out at five tertiary institutions. Based on post-campaign evaluation results, the campaign far exceeded the targets set by the team in its output and impact objectives. Ultimately, the campaign earned $216,610 in PR value, reaching 404,973 total online impressions and 12,134 total online engagements. Young people exposed to the campaign showed an overall increase in (i) anti-phishing knowledge, (ii) perceived threat susceptibility, (iii) perceived threat severity, (iv) self-efficacy of adopting anti-phishing behaviour, (v) response efficacy of adopting anti-phishing behaviour, and (vi) intention to adopt anti-phishing behaviour, as compared to non-exposed young adults. A discussion on the campaign’s implications, limitations, and sustainability is included at the end of this paper. Original documents and relevant data can be found in the appendices as references to the main paper.